SER PROFESSOR: UM ESTUDO SOBRE A CONSTITUIÇÃO IDENTITÁRIA PROFISSIONAL DO ENFERMEIRO DOCENTE - Braga, Maria Jacinta Gomes (2013)
The present study was developed with the goal of understanding the construction of the professional identity of nursing teachers of undergraduate nursing from a private institution located in the city of São Paulo. The discussion of the processes of identity formation was based on studies of Placco Vera de Souza, nationally, and Maurice Tardif and Claude Dubar, internationally. In an exploratory stage, we applied a semi-structured questionnaire to five teachers of graduate studies in Nursing and held a semi-directive with two of the participants in order to refine the data collection instruments. The main research made use of interviews with seven teachers of undergraduate degree in Nursing from the same institution. The data from both the exploratory study as the primary research were analyzed with reference to the assumptions of systematic content analysis by Laurence Bardin and Maria Laura P. B. Franco. The results indicated that nurses become teachers driven by the desire to teach and share knowledge, job opportunities, flexible hours and completion of professional income, and are influenced by their teachers and family formation trajectory. The characteristics valued by them at a teacher were: mastery of content taught, especially the technical knowledge, the continuous pursuit of knowledge, ethics, professionalism, humanization. It is noted a preponderance of the characteristics that involve the knowledge of the content at the expense of pedagogical issues. The reflection and concern about Teaching are present in their speech, as the constant quest to overcome the difficulties in the profession. They consider Teaching profession as a role of prominence in the same way that Nursing. Another factor highlighted in the responses was the strong representation of nurses in the professional career of respondents. In their reports, it was revealed that the construction as teachers occurs continuously throughout the career, which is evident in their speech when they claim to be better teachers now than earlier, despite being a prickly walk initially, it became pleasurable and significant over time. It is emphasized here the importance of valuing the knowledge of the teacher, because only starting with this knowledge, plus theoretically and conceptually working it, teachers will be able to expand the understanding of the work process in health that, now a days, has become highly complex.